2017
DOI: 10.5603/kp.a2017.0033
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of three-dimensional printed heart models for operative planning of complex congenital heart defects

Abstract: A b s t r a c t Background and aim:To evaluate the accuracy of the three-dimensional (3D) printing of cardiovascular structures. To explore whether utilisation of 3D printed heart replicas can improve surgical and catheter interventional planning in patients with complex congenital heart defects. Methods:Between December 2014 and November 2015 we fabricated eight cardiovascular models based on computed tomography data in patients with complex spatial anatomical relationships of cardiovascular structures. A Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 11 publications
2
55
0
Order By: Relevance
“…Of the 28 articles, 17 of them (61%) were case reports and case series, based on number of cases ranging from 1 to 12 cases with different CHD and cardiovascular diseases. Ten of them (36%) were cross‐sectional studies, mainly surveying the healthcare professionals, parents, parents of patients and medical students; and 3 of which were randomised controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 articles, 17 of them (61%) were case reports and case series, based on number of cases ranging from 1 to 12 cases with different CHD and cardiovascular diseases. Ten of them (36%) were cross‐sectional studies, mainly surveying the healthcare professionals, parents, parents of patients and medical students; and 3 of which were randomised controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…Only 6 studies reported on the dimensional accuracy of the models . Overall, good to excellent correlation in measurements was found between the 3D printed heart models and original medical images or intra‐operative surgical measurements, indicating that 3D printed models have high accuracy in replicating complex cardiac anatomical structures and pathologies (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations